The Pottery Manufacturing Process and Business Model: (Case Study : MuseumKu Gerabah In Kasongan, Bantul, Yogyakarta) - Agung Purnomo; Ryan Mahfud Hidayat; Husnan Rizky Ramadhan; Her Tafga Arfanindita; Anirawilda Purba; Bina Arumbinang Wajdi (Yayasan Inovasi Kemajuan Intelektual, 2026)
This study aims to analyse the manufacturing process, business model, and sustainability aspects of MuseumKu Gerabah in Kasongan, Bantul. A descriptive qualitative case study approach was employed through observation, semi-structured interviews, and document analysis. The findings reveal that the manufacturing process consists of four main stages: material preparation, forming (hand-forming, moulding, and wheel-throwing), drying, and traditional kiln firing using wood and straw. Wheel-throwing is identified as the primary training method due to its high replicability and transferable skills. The Business Model Canvas (BMC) analysis highlights strengths in cultural value, interactive experiential learning, and diversified revenue streams. However, challenges include the utilisation of traditional firing technology, limited digital integration, and ageing artisans. Thematic analysis indicates interconnected cultural, social, and environmental sustainability dimensions, although environmental performance requires improvement through greener technology adoption and digital transformation. Theoretically, this study integrates traditional manufacturing analysis, business model evaluation, and sustainable creative tourism frameworks.